Functional role of ambient GABA in refining neuronal circuits early in postnatal development - Cellot, Giada; Cherubini, Enrico (Frontiers in Neural Circuits, 2013)
Early in development, gamma-aminobutyric acid (GABA), the primary inhibitory neurotransmitter in the mature brain, depolarizes and excites targeted neurons by an outwardly directed flux of chloride, resulting from the peculiar balance between the cation-chloride importer NKCC1 and the extruder KCC2. The low expression of KCC2 at birth leads to accumulation of chloride inside the cell and to the equilibrium potential for chloride positive respect to the resting membrane potential. GABA exerts its action via synaptic and extrasynaptic GABAA receptors mediating phasic and tonic inhibition, respectively. Here, recent data on the contribution of "ambient" GABA to the refinement of neuronal circuits in the immature brain have been reviewed. In particular, we focus on the hippocampus, where, prior to the formation of conventional synapses, GABA released from growth cones and astrocytes in a calcium- and SNARE-independent way, diffuses away to activate in a paracrine fashion extrasynaptic receptors localized on distal neurons. The transient increase in intracellular calcium following the depolarizing action of GABA leads to inhibition of DNA synthesis and cell proliferation. Tonic GABA exerts also a chemotropic action on cell migration. Later on, when synapses are formed, GABA spilled out from neighboring synapses, acting mainly on extrasynaptic5, 2, 3 and  containing GABAA receptor subunits, provides the membrane depolarization necessary for principal cells to reach the window where intrinsic bursts are generated. These are instrumental in triggering calcium transients associated with network-driven GDPs which act as coincident detector signals to enhance synaptic efficacy at emerging GABAergic and glutamatergic synapses.